Natural Language Processing in Computational Communication Research - Li, Chenxi; Lian, Shuguo (Journal of Theory and Practice in Engineering and Technology, 2024)
The rapid development of information technology has made the paradigm shift in communication studies increasingly evident, leading to a growing reliance on text data mining techniques in disciplinary research. This satisfies the developmental requirements of computational communication studies. This paper explores natural language processing (NLP) techniques, analyzing their role in integrating these technologies into computational communication research. The following conclusion is drawn: In the context of global information globalization, NLP technology is advantageous in addressing disciplinary issues.